Molecular and Structural Basis of DNA Sensors in Antiviral Innate Immunity - Zahid, Ayesha; Ismail, Hazrat; Li, Bofeng; Jin, Tengchuan (Frontiers in Immunology, 2020)
DNA viruses are a source of great morbidity and mortality throughout the world by causing many diseases; thus, we need substantial knowledge regarding viral pathogenesis and the host's antiviral immune responses to devise better preventive and therapeutic strategies. The innate immune system utilizes numerous germ-line encoded receptors called pattern-recognition receptors (PRRs) to detect various pathogen-associated molecular patterns (PAMPs) such as viral nucleic acids, ultimately resulting in antiviral immune responses in the form of proinflammatory cytokines and type I interferons. The immune-stimulatory role of DNA is known for a long time; however, DNA sensing ability of the innate immune system was unraveled only recently. At present, multiple DNA sensors have been proposed, and most of them use STING as a key adaptor protein to exert antiviral immune responses. In this review, we aim to provide molecular and structural underpinnings on endosomal DNA sensor Toll-like receptor 9 (TLR9) and multiple cytosolic DNA sensors including cyclic GMP-AMP synthase (cGAS), interferon-gamma inducible 16 (IFI16), absent in melanoma 2 (AIM2), and DNA-dependent activator of IRFs (DAI) to provide new insights on their signaling mechanisms and physiological relevance. We have also addressed less well-understood DNA sensors such as DEAD-box helicase DDX41, RNA polymerase III (RNA pol III), DNA-dependent protein kinase (DNA-PK), and meiotic recombination 11 homolog A (MRE11). By comprehensive understanding of molecular and structural aspects of DNA-sensing antiviral innate immune signaling pathways, potential new targets for viral and autoimmune diseases can be identified.